The Effect Of Repressive Supervision And Work Culture On Employee Work Productivity At Pt Global Offset Sejahtera - Karunia, Intan Dwi; Pratama, Devangga Putra Adhitya; Ayi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The Influence of Repressive Supervision and Work Culture on Employee Productivity (Case Study at PT Global Offset Sejahtera), Sekolah Tinggi Ilmu Ekonomi Pemuda, Advisor Devangga Putra Adhitya Pratama, S.Pd., M.Pd. The purpose of this study is to determine and analyze the influence of repressive supervision and work culture on employee productivity at PT Global Offset Sejahtera. Repressive supervision is a form of supervision conducted after an activity has been completed. Its purpose is to evaluate and control work results to ensure they meet established standards. Work culture reflects the values, attitudes, and work behaviors adopted by employees within the company environment. The research method used is quantitative with a descriptive and associative approach, while the type of data used is primary data collected through the distribution of questionnaires to 200 respondents who are employees of PT Global Offset Sejahtera.Data modeling using multiple linear regression with the SPSS program. The results of this study indicate that repressive supervision and work culture have a significant simultaneous effect on work productivity. Similarly, both factors also have a positive and significant partial influence on employee productivity. The results indicate that the implementation of effective supervision and a conducive work culture will impact employee performance in terms of productivity.